Chemically deposited ZnS thin film as potential X-ray radiation sensor. (April 2017) - Sarma, M.P.; Kalita, J.M.; Wary, G.
Abstract: In this article X-ray radiation sensitivity of ZnS thin film prepared by a chemical bath deposition technique has been reported. The films were prepared under 0.10, 0.15 and 0.20 molarity (M). Characterization reports show that the 0.20 M film has the best quality than the other low molarity films. I-V characteristics of the films were studied under dark condition and observed that the film prepared at 0.20 M has an electrical conductivity of 2.06×10 −6 (Ω cm) −1 which is about 10 times greater than the other lower molarity films. Further, the I-V characteristic of this film has studied under UV and X-ray radiations. The current under X-ray radiation is found to be significantly higher than that under the UV radiation. At a fix bias voltage of 1.0 V, the conductivity under UV radiation is found to be 3.26×10 −6 (Ω cm) −1 whereas that under the X-ray is 4.13×10 −5 (Ω cm) −1 . The sensitivity under X-ray radiation is significantly greater than that under the UV radiation. This analysis suggests that the ZnS thin film which is used as a UV radiation sensor can also be used as a potential X-ray radiation sensor.